Effects of irrigation water regime, soil clay content and their combination on growth, yield, and water use efficiency of rice grown in South China - Hamoud, Yousef Alhaj; Guo, Xiangping; Wang, Zhenchang; Chen, Sheng; Rasoul, Gulam (International Journal of Agricultural and Biological Engineering, 2018)
To investigate the effect of irrigation regime, soil clay content and their combination on growth, yield, and water productivity of rice, a shelter experiment was conduct using Randomized Complete Block Design (RCBD) with a factorial arrangement of treatments with four replications. Irrigation regime was the main treatment investigated, set in three levels as R(30 mm-100%) (100% of saturation and 30 mm flooded), R(30 mm-90%) (90% of saturation and 30 mm flooded) and R(30 mm-70%) (70% saturation and 30 mm flooded), respectively. The sub-treatment was soil type, set in three levels as 40%, 50% and 60% clay content, respectively. Results showed that irrigation regime and soil clay content had significant effects on growth, yield and water productivity of rice. However, their combination showed no significant impact on panicles number, root biomass, harvest index and irrigation water productivity. Higher soil clay content results in increase in growth, yield, and water productivity of rice. The total water consumption during R(30 mm-100%) was higher than that during R(30 mm-90%) and R(30 mm-70%) because the latter two saturation levels led to the cracking of soil and decrease of total number of irrigations. Cracks were consistently getting more serious with the reduction in soil water content and the increase in soil clay content. Cracks in soil will preferentially become the major routes of water losses, thus water percolation during R(30 mm-70%) was higher than that during R(30 mm-90%) and R(30 mm-100%) after each irrigation event. The total water use under R(30 mm-70%) exceeded the water consumption under R(30 mm-90%) due to the great amount of soil cracking as well as the excessive volume of standing water depth. Considering water consumption and grain yield, the following conclusion can be reached: (i) The reduction in water consumption was greater than the reduction in grain yield in the case of drying soil 10% below saturation before reflooding. (ii) The reduction in water consumption was less than the reduction in grain yield in the case of drying soil 30% below saturation before reflooding; (iii) The increase in water use was greater than the increase in grain yield in the case of maintaining soil moisture at 100% of saturation before reflooding. Therefore, the water use efficiency was recorded in the order of R(30 mm-90%) >R(30 mm-100%) >R(30 mm-70%). Keywords: irrigation regime, clay content, combination, growth, yield, water productivity, rice DOI: 10.25165/j.ijabe.20181104.3895 Citation: Hamoud Y A, Guo X P, Wang Z C, Chen S, Rasool G. Effects of irrigation water regime, soil clay content and their combination on growth, yield, and water use efficiency of rice grown in South China. Int J Agric & Biol Eng, 2018; 11(4): 144-155.